English for radiology residency: Challenges and technology-based assistance - Kurniawati, Atin; Hanafi, Muchtar (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
This article tried to shed some light on how a radiology resident experienced challenges in using English during his study. Employing narrative inquiry, the data were collected from semi-structured interviews with a radiology resident currently studying at a state university in Indonesia. Meaningful experiences and insights were highlighted and elaborated. They were also discussed and corresponded with previous studies or existing theories. Understanding English textbooks with unfamiliar words made him spend longer time to understand English written materials. He was also required to publish articles in reputable journals and present papers in scientific forums. Meanwhile, he didn't have enough time due to his busy schedule at the hospital. He pointed out that basic English knowledge might helpful in the beginning, but once it got into specialty field of radiology there were many new terms to learn. Besides, willingness to learn English with fellow residents and from supporting tools were essential for success. He found some online tools very beneficial to make his work much easier and faster. However, those tools were still limited in some aspects and face-to-face learning activity was still needed. It implies the need for ESP learning design for busy residents which accommodates digital tools optimization and practical academic purposes.